PERAN PEMBELAJARAN MATA KULIAH ENTREPRENEURSHIP DALAM MENINGKATKAN MINAT BERWIRAUSAHA MAHASISWA UNIVERSITAS BHINNEKA PGRI TULUNGAGUNG - Pradana, Agil Surya; Rini Rindrayani, Sulastri; Kadeni (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study was motivated by the importance of the Entrepreneurship course in enhancing students' entrepreneurial interest through learning that integrates theory and practice. The objectives of this study were: (1) describe the Entrepreneurship course in instilling entrepreneurial values; (2) analyze the factors influencing students' entrepreneurial interest; and (3) identify the supporting and inhibiting factors in implementing the Entrepreneurship course at Universitas Bhinneka PGRI Tulungagung. This study employed a qualitative descriptive approach. The research subjects consisted of 24 sixth-semester students from eight study programs, four Entrepreneurship course lecturers, one Coordinator of the Entrepreneurship Course Cluster, and one Head of the Student Affairs, Career, Entrepreneurship, and Alumni Unit (OKWA). Data were collected through interviews, observations, and documentation, and were analyzed using the interactive analysis model of Miles, Huberman, and Saldaña. The findings revealed that the Entrepreneurship course was implemented through the stages of planning, implementation, and evaluation by integrating theoretical and practical learning, which successfully instilled entrepreneurial values in students. The learning factors that contributed to enhancing students' entrepreneurial interest included direct learning practices, experiential learning through observations of business and industrial sectors, and Project Based Learning. Supporting factors included lecturer mentoring, a curriculum integrating theory and practice, and from the OKWA Unit through various Entrepreneurship programs. Meanwhile, the inhibiting factors included limited business capital and students' time management. In conclusion, the Entrepreneurship course plays an important role in enhancing students' entrepreneurial interest through the integration of theory and practice.